Analysis of the Workload and Workforce Needs of Registration Officers Hospital - Hesty Latifa Noor; Paweena Wongsatho; Agus Sulistyawan; Nasuka Prabowo Aji (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Preparation of human resource requirements planning health, it is determined that the need for human resources is the number of human resources according to the type needed to carry out the given workload. Planning for human resource requirements is a systematic process in an effort to determine the number, type, and qualifications of human resources needed in accordance with with the conditions of a region in order to achieve development goals health. The object of this research is the registration officer at the hospital. The purpose of this study is to calculate the number of workforce needs in the registration section by Analysis Method Health Workload (ABK Kes). From several meanings, it can be concluded that needs planning human resources is a systematic process in an effort to determine, amount, and qualifications of human resources needed in accordance with the conditions of a region in order to achieve health development goals. After calculating the workload of the on-site officers, registration using the ABK Kes formula, researchers get results the registration section needs as many as 24 people. Meanwhile, there are 18 registration officers for the PKU Aisyiyah Singkil Hospital, Boyolali. This is not in accordance with the calculation of the workload that the researchers calculated using the ABK Kes formula. So it is necessary to add 6 registration officers to meet the needs of registration officers at PKU Aisyiyah Singkil Hospital, Boyolali